CYCLE pilot: a protocol for a pilot randomised study of early cycle ergometry versus routine physiotherapy in mechanically ventilated patients. Issue 4 (8th April 2016) - Kho, Michelle E; Molloy, Alexander J; Clarke, France; Herridge, Margaret S; Koo, Karen K Y; Rudkowski, Jill; Seely, Andrew J E; Pellizzari, Joseph R; Tarride, Jean-Eric; Mourtzakis, Marina; Karachi, Timothy; Cook, Deborah J; et al.
Abstract : Introduction: Early exercise with in-bed cycling as part of an intensive care unit (ICU) rehabilitation programme has the potential to improve physical and functional outcomes following critical illness. The objective of this study is to determine the feasibility of enrolling adults in a multicentre pilot randomised clinical trial (RCT) of early in-bed cycling versus routine physiotherapy to inform a larger RCT. Methods and analysis: 60-patient parallel group pilot RCT in 7 Canadian medical-surgical ICUs. We will include all previously ambulatory adult patients within the first 0–4 days of mechanical ventilation, without exclusion criteria. After informed consent, patients will be randomised using a web-based, centralised electronic system, to 30 min of in-bed leg cycling in addition to routine physiotherapy, 5 days per week, for the duration of their ICU stay (28 days maximum) or routine physiotherapy alone. We will measure patients' muscle strength (Medical Research Council Sum Score, quadriceps force) and function (Physical Function in ICU Test (scored), 30 s sit-to-stand, 2 min walk test) at ICU awakening, ICU discharge and hospital discharge. Our 4 feasibility outcomes are: (1) patient accrual of 1–2 patients per month per centre, (2) protocol violation rate <20%, (3) outcome measure ascertainment >80% at the 3 time points and (4) blinded outcomes ascertainment >80% at hospital discharge. Hospital outcome assessors are blinded to group assignment, whereas participants, ICU physiotherapists, ICU caregivers, research coordinators and ICU outcome assessors are not blinded to group assignment. We will analyse feasibility outcomes with descriptive statistics. Ethics and dissemination: Each participating centre will obtain local ethics approval, and results of the study will be published to inform the design and conduct of a future multicentre RCT of in-bed cycling to improve physical outcomes in ICU survivors. Trial registration number: NCT02377830; Pre-results.